1997
DOI: 10.1128/aac.41.9.1961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foscarnet cream on experimental UV radiation-induced herpes labialis

Abstract: A topical 3% foscarnet cream formulation was evaluated for its ability to treat experimental UV radiation (UVR)-induced herpes labialis in a double-blind study. Healthy adult volunteers with a history of sunlight-induced herpes labialis were randomly assigned at four centers to receive either foscarnet cream (n = 152) or a vehicle control (n = 150). Following measurement of the minimal erythematous dose (MED), the subjects' lips were exposed to 4 MEDs of UV light. Subjects applied the cream on the UVR-exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In typical experimental UVR exposure protocols to date, therapy was begun before clinical lesion onset [19,20,28]. Initiation of therapy with an effective parenteral agent, such as acyclovir capsules, before or at the time of UVR exposure, completely prevents delayed lesions; however, if treatment is begun 48 h after UVR exposure, delayed lesions are not prevented but are less severe [19].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In typical experimental UVR exposure protocols to date, therapy was begun before clinical lesion onset [19,20,28]. Initiation of therapy with an effective parenteral agent, such as acyclovir capsules, before or at the time of UVR exposure, completely prevents delayed lesions; however, if treatment is begun 48 h after UVR exposure, delayed lesions are not prevented but are less severe [19].…”
Section: Discussionmentioning
confidence: 98%
“…UVR-induced lesions tend to be more severe, providing a larger "target" to test chemotherapy [27]. Experimental UVR-induced lesions can be divided into delayed and immediate lesions: The delayed lesions can be completely prevented with prophylactic antiviral therapy and have responded with reduced lesion severity to episodic treatment with topical or systemic antiviral agents [19,20,28]. Post-UVR immediate lesions have not responded to antiviral treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59] An experimental studies was done on healthy adult human volunteer, have a history of sunlight-induced Herpes labialis. Lips of these subjects were then exposed to ultra violet light and immediately after exposure, cream was applied approximately eight times daily for 7 days.…”
Section: Antiviral Drugsmentioning
confidence: 99%
“…Randomized controlled trials of topical foscarnet 3% cream, applied four times daily, vs placebo have demonstrated that it can reduce the duration of virus shedding, development of vesicles and duration of ulcers (Lawee et al , 1988; Bernstein et al , 1997).…”
Section: Management Of Recurrent Hsv‐1 Infectionmentioning
confidence: 99%